Analisis Pengaruh Harga, Word Of Mouth Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Restoran Seafood Syurga Medan - Denni Denni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to find out the relationship of price variables, word of mouth and product quality to consumer purchasing decisions at Restaurant Seafood Syurga Medan. The purchase decision is a consideration made by the consumer before deciding to buy or consume a good or service in a certain place. In this study, it analyzes about the price, word of mouth and quality of the product that is supposed to affect consumer purchase decisions. The research uses descriptive analysis methods, classical assumption tests, double linear regression tests, partial tests (T-tests), simultaneous significance tests (F-testes) and determination coefficients (R2) with the help of Software Statistical Program of Social Science (SPSS) version 26 for Windows. The objects of the study are 90 people consumer. The results of the analysis show that simultaneously price, word of mouth and product quality influence consumer decisions on seafood dining house of Syurga city of Medan. Results of the determination coefficient testing showed the influence of price variables, Word of Mouth and quality of products on consumer purchasing decisions with an influence contribution of 53% and the remaining 47% are influenced by other variables outside the research such as promotional factors, customer service, appearance, road access and so on. Keywords : Price, Word Of Mouth, Product Quality, Purchasing Decisions